Towards universal access : strengthening the multi-sectoral coalition : acting responsibly in the prevention of HIV/AIDS - Bernard, Justice Desiree P. (CCS GeorgetownGY, 2009)
Focuses on ways in which HIV/AIDS can be prevented. Congratulates PANCAP on its work in this area and calls for continuous financial investment in PANCAP.